PERSONAL FINANCIAL MANAGEMENT IN THE DIGITAL ECONOMY ERA: FINANCIAL KNOWLEDGE, FINANCIAL BEHAVIOR AND FINANCIAL QUOTIENT - Riyani, Diah; Rosady, Febry; Hendarti, Yanita (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This research aims to analyze the influence of knowledge, behavior and financial intelligence on personal financial management in the digital economy era. This research is a literature study of actual problems that exist in society today. The approach used in this research is a qualitative approach, while the type of research used is library research (Bakker & Zubair, 1994). The object of this research is the influence of financial knowledge, financial behavior and financial intelligence on personal financial management in the digital economy era. Analyst results showBy combining these three aspects, individuals can achieve more robust personal financial management amidst the changes and complexity of the digital economy. Learning financial knowledge, developing good financial behavior, and increasing financial intelligence are key steps to achieving financial stability, achieving financial goals, and improving the quality of life in the dynamic digital economy era.